Analysis of BPJS Mandiri Participant Contribution Payment Compliance Inpatient Service Fines at Dr Mohamad Saleh Probolinggo Regional Hospital - Wardani, Umi Kusuma; Hernawati, Sri; Dewanto, Iwan (Masters Program in Public Health, Universitas Sebelas Maret, Indonesia, 2025)
Background: The National Health Insurance Program (JKN) through BPJS Kesehatan is an initiative to equalize the quality of health services for all levels of society. Contributions are an essential factor in the success of a national social security system. The importance of paying BPJS contributions regularly is so that participants get adequate health service guarantees. The study aims to analyze the compliance of BPJS Mandiri participant contribution payments who are subject to inpatient service fines at Dr. Mohamad Saleh Probolinggo Regional Hospital. Subjects and Method: An observational study with a cross-sectional approach was conducted in the inpatient unit of Dr. Mohamad Saleh Hospital, Probolinggo, in May and June 2023. A total of 100 patients were selected for this study. The dependent variable was compliance. The independent variables were knowledge, income, number of family members, perception of illness, access to health services. Data were collected using a questionnaire and analyzed using factor analysis, t-test, f-test and multiple linear regression. Results: The regression coefficient of knowledge variable is 0.018, income is 0.823, number of family members is 0.375, perception of illness is -0.021, access to health services is -0.128. Compliance of contribution payments is influenced by income variable with sig 0.002, number of family members with sig (0.000) and access to health services with sig (0.007). Conclusion: Compliance in payment of BPJS Mandiri participants who are subject to inpatient service fines is influenced by income, number of family members, access to health services. The most dominant factor is income.